Comparative Analysis of Early Life Stage Traits in Annual and Perennial Phaseolus Crops and Their Wild Relatives - Herron, Sterling A.; Rubin, Matthew J.; Ciotir, Claudia; Crews, Timothy E.; Van Tassel, David L.; Miller, Allison J. (Frontiers in Plant Science, 2020)
Herbaceous perennial species are receiving increased attention for their potential to provide both edible products and ecosystem services in agricultural systems. Many legumes (Fabaceae Lindl.) are of special interest due to nitrogen fixation carried out by bacteria in their roots and their production of protein-rich, edible seeds. However, herbaceous perennial legumes have yet to enter widespread use as pulse crops, and the response of wild, herbaceous, perennial species to artificial selection for increased seed yield remains under investigation. Here we compare cultivated and wild accessions of congeneric annual and herbaceous perennial legume species to investigate associations of lifespan and cultivation with early life stage traits including seed size, germination, and first year vegetative growth patterns, and to assess variation and covariation in these traits. We use “cultivated” to describe accessions with a history of human planting and use, which encompasses a continuum of domestication. Analyses focused on three annual and four perennial species of the economically important genus Phaseolus. We found a significant association of both lifespan and cultivation status with seed size (weight, two-dimensional lateral area, length), germination proportion, node number, stem diameter, shoot dry mass, and root dry mass. For wild accessions, annual and perennial traits were largely similar, although germination was significantly higher in annuals. Relative to wild forms, both cultivated annual and cultivated perennial accessions exhibited greater seed size and larger overall vegetative size, with cultivated perennials showing greater mean trait differences relative to wild accessions than cultivated annuals. Germination proportion was significantly lower in cultivated relative to wild annual accessions, while no difference was observed between cultivated and wild perennial germination. Seed size traits were positively correlated with most vegetative growth traits, and all biomass traits examined here were positively correlated. This study highlights some fundamental similarities and differences between annual and herbaceous perennial legumes and provides insights into how perennial legumes might respond to artificial selection compared to annual species.